Nordic Forest Energy Solutions in the Republic of Karelia - Yuri Gerasimov; Sergei Senko; Timo Karjalainen (Forests, 2013)
The situation in Karelia, a region in Northwest Russia, is analyzed in the context of forest energy. The annual potential energy available from wood harvesting is about 7 tera watt hours (TWh) (3.6 million m3), which is equal to the total need of Karelia in energy for municipal heating. We point out that the contribution to the municipal economy, the moderate heating cost, the enhanced energy security in the cold Russian climate, the environmental friendliness, the better access to the forests and the utilization of the proven Nordic forest energy solutions (NFES) might have important consequences for strategy-making processes in forest energy development. For this purpose, connecting Analytic Hierarchy Process (AHP) with SWOT (internal strengths (S) or weaknesses (W) and external opportunities (O) or threats (T)) analysis is proposed to identify local operational strategies and assign priorities. Major threats include lack of government support, an insufficient road network, the dominance of extensive forest management, gasification and financial indiscipline. Analysis indicates that NFES are viewed positively for the Russian conditions. The forest biomass market has virtually unlimited opportunities for growth. Together, with the transition to intensive forest management, favorable policy in terms of forestry development programs can support bioenergy development. The advantageous location of existing power plants next to forests, increasing fossil fuel prices, the improvement of the road network and the availability of new technology are seen as potential opportunities for NFES. However, the results also indicate that there is substantial uncertainty and skepticism concerning how such markets benefit forest leaseholders who would like to adopt forest energy. The lack of bioenergy technology development, high transportation cost, low awareness of NFES, high demands for roads, the requirement for skilled specialists and wood fuel quality are the main weaknesses regarding the transfer of NFES to Karelia.